STUDENTS’_ DIFFICULTIES IN SPEAKING ENGLISH: (A Case Study in SMKN 3 Sorong) - Ester Maji; Udi Samanhudi; Maryanti E Mokoagouw (LPPM Politeknik Saint Paul Sorong, 2022)
This study aims to investigate the difficulties and the cause encountered by students of vocational school SMKN 3 Sorong while speaking English. It was used a case study research design which employed two data collection techniques, namely: class observations and interviews. This study has indicated that the main difficulties encountered by student while speaking English were caused by linguistic factors, for instance: lack of vocabularies, poor pronunciation and lack of grammar knowledge. The second problem that students have while speaking English was caused by nonlinguistic factors (psychological factors), for instance: fear of making mistake, low motivation, shyness, anxiety, mother tongue use. However, the psychological factors contributed less than linguistics factors. In conclusion that linguistic factor is the most dominant difficulties encountered by the twelfth year students of SMKN 3 Sorong while speaking English